Cost-Plus Pricing Strategy at Hanif Jaya Motor Workshop Jatibarang-Indramayu - Rachman , Soraya Hanif; Junipriansa, Donni (Journal La Bisecoman, 2024)
The work aims to evaluate the applied pricing policies in the Indonesia automotive repair market to analyse the decision making of Hanif Jaya Motor Workshop which is an SME company. The research is centered on the effects of intuition pricing on the price determination, issues of cost control and the role of competition in pricing. Investigating the use of informal experience-based judgment and intuitive decision making at the workshop, as expected, has its advantages of flexibility, but the research findings show that they are dangerous for long-term profit making. The study draws public attention to these weaknesses, the most significant being the inability to capture cost increases and market dynamics and set suboptimal price to ruin the financial sustainability of service provision. The research also brings to light that the management of costs also poses a challenge at the workshop; efforts to offer competitive prices by increasing the internal costs have been associated with compromise on the strength of the products. Alas, this is quite dangerous not only for customer satisfaction but also for the degradation of a business’s reputation. Moreover, the study shows the negative impact of involvement in price concussion and portends that SMEs could proposed for better results by moving to value-based rather than cost-based pricing strategies.xThe implication for SMEs such as Hanif Jaya Motor Workshop is that it will be advantageous if cost based and value based elements are well structured and include more regularly data. They would help in the achievement of a closer fit with customers’ perceived value, improved competitiveness and business viability.